SAT0397 DESCRIPTIVE COMPARISONS OF THE IMPACT OF APREMILAST AND METHOTREXATE MONOTHERAPY ON PATIENTS WITH OLIGOARTICULAR PSORIATIC ARTHRITIS IN THE CORRONA PSORIATIC ARTHRITIS/SPONDYLOARTHRITIS REGISTRY. (June 2019) - Ogdie, Alexis; Liu, Mei; Glynn, Meghan; Emeanuru, Kelechi; Harrold, Leslie; Richter, Sven; Guerette, Benoit; Mease, Philip J.
Abstract : Background: Therapeutic effectiveness has rarely been studied in a subpopulation of patients with oligoarticular PsA. Objectives: To examine baseline characteristics and 6-month clinical assessments of PsA patients with oligoarthritis (≤4 swollen joints) who initiated apremilast (APR) or methotrexate (MTX) monotherapy in the Corrona PsA/SpA Registry, a prospective, US-based, observational cohort study. Patients initiating bDMARD monotherapy were also examined as a point of reference. Methods: Patients ≥18 years of age with PsA and oligoarthritis in the registry who initiated APR, MTX or a bDMARD (reference group) monotherapy and had a 6-month follow-up visit between June 2014 and March 2018 were included. Descriptive statistics were calculated for patients' clinical characteristics and disease assessments at treatment initiation and at the 6-month follow-up visit. Results: The analysis included 150 patients initiating therapy (APR: n=34; MTX: n=15; bDMARD: n=101). Among APR and MTX initiators, 79% and 20% received at least 1 prior bDMARD, respectively. APR initiators, compared with MTX initiators, were younger (mean [SD]: 55.7 [12.6] vs. 61.5 [16.6] years), had longer disease duration (mean [SD]: 8.0 [6.7] vs. 5.4 [7.8] years), and had higher levels of disease activity at baseline, including greater skin involvement (mean body surface area affected [SD]: 7.1% [17.6%] vs. 4.8% [9.4%]), swollen joint count (mean [SD]: 1.5 [1.5] vs. 1.0 [1.1]) and Clinical Disease Activity for Psoriatic Arthritis (cDAPSA) moderate and high disease activity (50% [APR] vs. 27% [MTX]; mean score [SD]: 14.0 [8.5] vs. 11.5 [4.9]). APR initiators also had greater disease impairments at baseline, represented by numerically higher scores on patient-reported outcome (PRO) measures, including the Health Assessment Questionnaire-Disability Index (HAQ-DI; mean [SD]: 1.0 [0.7] vs. 0.5 [0.4]), Patient's Global Assessment of Disease Activity–Psoriasis (PtGA-PsO; mean [SD]: 47.1 [29.4] vs. 28.4 [16.6]); Patient's Global Assessment of Disease Activity–Psoriatic Arthritis (PtGA-PsA; mean [SD]: 47.1 [29.8] vs. 32.5 [26.3]), fatigue (mean [SD]: 55.9 [30.0] vs. 37.8 [31.9]) and overall pain (mean [SD]: 50.5 [31.1] vs. 46.7 [26.5]). Taken together, results suggest that APR initiators had more refractory oligoarthritis compared with MTX initiators. Clinical assessments at the 6-month follow-up indicate that patients who initiated APR experienced numerically higher improvements in disease activity and various PRO measures compared with MTX, as well as achievement of ≤1 swollen joint, HAQ-DI minimal clinically important difference and cDAPSA remission or low disease activity (Table). Of note, results associated with bDMARDs were more comparable to that of APR. Conclusion: In this analysis of the Corrona PsA/SpA Registry, APR monotherapy was more often used in patients with refractory oligoarthritis compared with MTX monotherapy. Despite this, the APR treatment group experienced numerically greater improvements in disease activity measures. Improvements observed with APR treatment in patients with long-standing disease and refractory oligoarthritis were comparable to that of bDMARDs. Acknowledgement: This study was sponsored by Corrona, LLC. Corrona is supported through contracted subscriptions with multiple pharmaceutical companies. The abstract was a collaborative effort between Corrona and Celgene Corporation with financial support provided by Celgene. Disclosure of Interests: Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Mei Liu Employee of: M. Liu is an employee of Corrona, LLC., Meghan Glynn Employee of: M. Glynn is an employee of Corrona, LLC., Kelechi Emeanuru Employee of: Corrona, LLC, Leslie Harrold Shareholder of: Corrona, Grant/research support from: Pfizer, Consultant for: AbbVie, BMS, and Genentech, Employee of: Corrona, Sven Richter Employee of: Celgene Corporation, Benoit Guerette Employee of: Celgene Corporation, Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB